The Role of Ibn Farhat’s Linguistic Heritage in Overcoming Cultural and Linguistic Stagnation and the Formation of the Arab Renaissance - Ishankhanova, Muxlisabonu Turgunovna (The Lingua Spectrum, 2026)
This article analyzes the systemic crisis of Arabic culture from the 13th to 18th centuries and the pivotal role of Arab Christians in initiating the Arab Renaissance. The author explores the causes of stagnation in Muslim society, primarily the institutional dominance of taqlīd (imitation) and the widening gap between sacralized linguistic norms (fuṣḥa) and living speech. Central to the study is the scholarly contribution of the Maronite scholar Ibn Farhat, whose work bridged Western rationalism and Eastern tradition. Special focus is placed on his treatise «Baḥṯ аl-maṭālib wа ḥаṯṯ аl-ṭālib», which simplified Arabic pedagogy and integrated the language into the daily and liturgical practices of Christian communities. The paper emphasizes that the transition from Karshuni script to classical Arabic, alongside Ibn Farhat’s reforms, provided the ideological foundation for overcoming cultural isolation. It concludes that Lebanon’s Christian intellectuals, educated through European models like the Pontifical Maronite College, were the primary catalysts for modernizing Arabic philology and precursors to the 19th-century Enlightenment.